2022
DOI: 10.1186/s12870-022-03705-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GhABF3 increases cotton(Gossypium hirsutum L.) tolerance to salt and drought

Abstract: Background Plants suffer from various abiotic stresses during their lifetime, of which drought and salt stresses are two main factors limiting crop yield and quality. Previous studies have shown that abscisic acid (ABA) responsive element binding protein (AREB)/ ABRE binding factors (ABFs) in bZIP transcription factors are involved in plant stress response in an ABA-dependent manner. However, little is known about the properties and functions of AREB/ABFs, especially ABF3, in cotton. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…So far, the role of ABF2s from various plants in stress tolerance has been extensively illustrated. Overexpression of A. thaliana ABF2 or its homologous genes from other plants has revealed that the ABF2s function as master regulators for abiotic stress tolerance in an ABA‐dependent pathway (Guan et al ., 2009; Hossain et al ., 2010; Wang et al ., 2021; Zhang et al ., 2022a). However, it is worth mentioning that the physiological mechanism of the ABF2s in drought tolerance is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the role of ABF2s from various plants in stress tolerance has been extensively illustrated. Overexpression of A. thaliana ABF2 or its homologous genes from other plants has revealed that the ABF2s function as master regulators for abiotic stress tolerance in an ABA‐dependent pathway (Guan et al ., 2009; Hossain et al ., 2010; Wang et al ., 2021; Zhang et al ., 2022a). However, it is worth mentioning that the physiological mechanism of the ABF2s in drought tolerance is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the role of ABF2s from various plants in stress tolerance has been extensively illustrated. Overexpression of A. thaliana ABF2 or its homologous genes from other plants has revealed that the ABF2s function as master regulators for abiotic stress tolerance in an ABA-dependent pathway (Guan et al, 2009;Hossain et al, 2010;Zhang et al, 2022a). However, it is worth mentioning that the physiological mechanism of the ABF2s in drought tolerance is still poorly under-Previous studies demonstrated that ABF2s function as positive regulators of drought tolerance possibly by modulating proline biosynthesis, antioxidant activity, water use efficiency, and photosynthetic capacity (Zhao et al, 2016;Kerr et al, 2018).…”
Section: Ptrabf2 Functions In Drought Tolerance By Modulating Putresc...mentioning
confidence: 99%
“…In addition, regulatory elements in most HKT genes in S. alterniflora have more ABRE elements than in rice and Arabidopsis. Previous studies have shown that the ABRE element is involved in the salt stress response of plants (Liu et al, 2022;Narusaka et al, 2003;Zhang et al, 2022). It is plausible that the increased number of ABREs confers elevated salt tolerance to S. alterniflora.…”
Section: Gene Duplication Promoted the Expansion Of Hktsmentioning
confidence: 99%
“…ABSCISIC ACID RESPONSIVE ELEMENT‐BINDING FACTORs (ABFs) are TFs that are downstream targets of SnRK2s; these can be phosphorylated to activate the expression of target genes in the ABA signaling pathway. The GhABF3 gene can simultaneously increase tolerance to salt and drought in cotton (Zhang et al, 2022). Finally, the overexpression of an ABA‐induced cotton gene, GhCBF3 , enhanced drought and salinity tolerance in transgenic Arabidopsis (Ma et al, 2015).…”
Section: Cotton Functional Genomics: a Magic Weapon For Cotton Breedingmentioning
confidence: 99%